Historical Memory: The Struggle for the Miners’ Archive in Bolivia - John, S. Sándor (Labour / Le Travail, 2020)
The Miners' Archive [founded on the impetus of mine workers in 2000] remains little known outside Bolivia. Yet the story of its creation is part of the legacy of struggle and sacrifice by Bolivia's predominantly Indigneous working people and a vital contribution to collective memory by and for the working class, and for historians the world over. --From author's conclusion.